O-036 Incidence of technical difficulties during pipeline device deployment in the initial cohort of patients treated at a tertiary referral medical center. (4th July 2012) - Almandoz, J Delgado; Crandall, B; Fease, J; Scholz, J; Kadkhodayan, Y; Anderson, R; Tubman, D
Abstract : Purpose: To determine the incidence of technical difficulties during Pipeline device deployment in the initial cohort of patients treated at a tertiary medical center. Methods: We retrospectively identified all patients with cerebral aneurysms treated with the Pipeline device at our institution from November 17, 2011 until March 15, 2012. We then reviewed the medical records and treatment catheter angiograms to determine patient age, gender, ruptured/unruptured aneurysm status, maximum aneurysm dimension, neck size, location, technical difficulties during Pipeline deployment, use of Dyna-CTA, balloon-angioplasty, and the short-term clinical outcome at hospital discharge. The cohort was divided into two groups: group 1 comprised the first 10 on-label cases and group 2 the subsequent 13 cases. We then performed statistical analysis to determine if there was a statistically-significant difference in the incidence of technical difficulties during Pipeline deployment between the two groups (p value≤0.05). Results: 23 cerebral aneurysms in 22 patients were treated with the Pipeline device at our institution during our study's time period. 18 patients were female (81.8%) and four male (18.2%), with a mean age of 59.5 years (median 63 years, range 31–81 years). 22 aneurysms were unruptured (95.3%) and one was ruptured (4.3%). Aneurysm locations were: seven in the internal carotid artery (ICA) below the ophthalmic artery (30.4%), six in the periophthalmic ICA (26.1%), five in the supraclinoid ICA (21.7%), two in the middle cerebral artery (8.7%), one in the anterior cerebral artery (4.3%), one in the vertebral artery (4.3%), and one in the basilar artery (4.3%). Mean maximum aneurysm sac dimension was 11.4 mm (median 10 mm, range 2.1–27 mm) and mean aneurysm neck size was 5.6 mm (median 4.8 mm, range 1.4–17 mm). Mean number of Pipeline devices deployed was 1.3 (median 1, range 1–5). Dyna-CTA was performed in 15 cases (65.2%) and balloon angioplasty of the Pipeline construct to achieve adequate wall apposition was performed in five cases (21.7%). Technical difficulties during Pipeline deployment were encountered in five cases (21.7%): two stenoses within the Pipeline construct requiring balloon angioplasty (8.7%), two herniations of the Pipeline construct into the aneurysm (8.7%) requiring removal of the construct in one case and re-catheterization of the construct in one case, and one proximal endoleak requiring deployment of an additional Pipeline device (4.3%). In one patient a residual stenosis in the Pipeline construct caused an infarction leading to a new permanent neurological deficit (4.3%). There was a trend toward a higher incidence of technical difficulties during Pipeline device deployment in the first 10 on-label cases (40%) compared to the subsequent 13 cases (7.7%) performed at our institution (p value 0.13, Abstract O-036 table 1 ). Conclusion: The incidence of technical difficulties during deployment of the Pipeline device appears to decrease with decreasing maximum aneurysm sac and neck size as well as increasing operator experience. Competing interests: J Delgado Almandoz: None. B Crandall: ev3/Covidien. J Fease: None. J Scholz: None. Y Kadkhodayan: None. R Anderson: None. D Tubman: ev3/Covidien.